Luminescent quantum dot films improve light use efficiency and crop quality in greenhouse horticulture - Hebert, Damon; Boonekamp, Jeroen; Parrish, Charles H.; Ramasamy, Karthik; Makarov, Nikolay S.; Castañeda, Chloe; Schuddebeurs, Lisanne; McDaniel, Hunter; Bergren, Matthew R. (Frontiers in Chemistry, 2022)
The spectral quality of sunlight reaching plants remains a path for optimization in greenhouse cultivation. Quantum dots represent a novel, emission-tunable luminescent material for optimizing the sunlight spectrum in greenhouses with minimal intensity loss, ultimately enabling improved light use efficiency of plant growth without requiring electricity. In this study, greenhouse films containing CuInS2/ZnS quantum dots were utilized to absorb and convert ultraviolet and blue photons from sunlight to a photoluminescent emission centered at 600 nm. To analyze the effects of the quantum dot film spectrum on plant production, a 25-week tomato trial was conducted in Dutch glass greenhouses. Plants under the quantum dot film experienced a 14% reduction in overall daily light integral, resulting from perpendicular photosynthetically active radiation transmission of 85.3%, mainly due to reflection losses. Despite this reduction in intensity, the modified sunlight spectrum and light diffusion provided by the quantum dot film gave rise to 5.7% improved saleable production yield, nearly identical total fruiting biomass production, 23% higher light use efficiency (g/mol), 10% faster vegetative growth rate, and 36% reduced tomato waste compared to the control, which had no additional films. Based on this result, materials incorporating quantum dots show promise in enabling passive, electricity-free spectrum modification for improving crop production in greenhouse cultivation, but extensive controlled crop studies are needed to further validate their effectiveness.